Performing Masculinity Through Christian Devotion: Methodism, Manhood and Colonial Mimicry in Fiji. Issue 1 (2nd January 2016) - Presterudstuen, Geir Henning
Abstract : Although the academic research on religion in Fiji and the South Pacific is substantial, there are few examples of studies that connect religion with the larger discourses of Fijian tradition and social life. Even fewer are the ones linking culturally specific notions of gender performances to Christian devotion. By utilizing the theoretical framework of colonial mimicry, 1 I argue that the Christianization of Fiji, particularly its continued impact on the social organization of modern Fijian society, has been reliant upon its collusion with premodern Fijian notions of gender, power and consanguinity. Based on historical enquiries and ethnographic material, I develop the argument that while conversion may be understood as the conscious adoption and mimicking of the western notion of religion as presented by Wesleyan missionaries in the 1800s, the Fijian understanding of their Christianity, the merging between Christian belief and Fijian social protocol and the consequent development of culturally specific articulations of Christian devotion have produced substantial differences from western theological practice and teaching. A central distinction is the close link between performances of masculinity and Christian devotion found among Fijian Methodists.